2020
DOI: 10.1177/1076029620971053
|View full text |Cite
|
Sign up to set email alerts
|

The Risk Factors of VTE and Survival Prognosis of Patients With Malignant Cancer: Implication for Nursing and Treatment

Abstract: Venous thromboembolism (VTE) is very common in patients with malignant cancer. We aimed to conduct a retrospective analysis on the risk factors of VTE and its survival prognosis of patients with malignant cancer, to provide evidence into the management of VTE. Patients with malignant cancer treated in our hospital were selected. The characteristic of patients and related lab detection results including activated partial thromboplastin time (APTT), plasma prothrombin time (PT) and thrombin coagulation time (TT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…For patients with cancer, in addition to coping with the burden of their tumor(s), venous thromboembolism (VTE) may develop as a complication, resulting in a worsened prognosis and increased mortality risk [1,2]. Cancer patients have a 5-fold higher risk of developing VTE than healthy individuals (annual incidence of 0.5% vs. 0.1%) [3].…”
Section: Introductionmentioning
confidence: 99%
“…For patients with cancer, in addition to coping with the burden of their tumor(s), venous thromboembolism (VTE) may develop as a complication, resulting in a worsened prognosis and increased mortality risk [1,2]. Cancer patients have a 5-fold higher risk of developing VTE than healthy individuals (annual incidence of 0.5% vs. 0.1%) [3].…”
Section: Introductionmentioning
confidence: 99%
“…3 For patients with cancer, in addition to coping with the burden of their tumor(s), venous thromboembolism (VTE) may develop as a complication, resulting in a worsened prognosis and increased mortality risk. 4,5 The mechanism by which cancer patients are at increased risk of developing VTE is complex and is thought to involve a combination of factors. 6 It is known that in cancer patients, cancer cells can activate hemostasis through multiple pathways and thereby induce systemic hypercoagulability.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, colorectal cancer was the most common malignancy in Japan, affecting >148,500 people and causing >59,000 deaths 3 . For patients with cancer, in addition to coping with the burden of their tumor(s), venous thromboembolism (VTE) may develop as a complication, resulting in a worsened prognosis and increased mortality risk 4,5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Of these, 11 studies reported data on F1.2 15,19,[25][26][27][28][29][30][31][32][33] (►Table 2), nine studies reported data on TAT [25][26][27]30,[33][34][35][36][37] (►Table 3), and 12 studies reported data Embase ('malignant neoplasm'/exp OR cancer à OR neoplasm à OR malignanc à ) AND ('thromboembolism'/exp OR "venous thromboembolism" OR "venous thrombo-embolism" OR "venous thrombosis" OR "deep vein thromboembolism" OR "deep vein thrombosis" OR "portal thrombosis" OR "sinus thrombosis" OR "mesenterial thrombosis" OR "cerebral vein thrombosis" OR "cancer-associated thrombosis" OR "VTE" OR "DVT") AND ('thrombin'/exp OR 'thrombography'/exp OR "thrombin" OR "calibrated automated thrombogram" OR "thrombography" OR "prothrombin" OR 'thrombin antithrombin complex'/exp OR "TAT" OR "thrombinantithrombin") NOT 'conference abstract'/it on thrombin generation 13,21,28,29,31,[38][39][40][41][42][43][44] (►Table 4). Of the 24 included papers, 13 were rated as good, eight as fair, and three studies were rated as poor.…”
Section: Resultsmentioning
confidence: 99%